Personal Video Recorder Function Based on Android Platform Set-top Box - Jing Dai; Kewen Xia; Zhong Hua; Zhiqiang Kou (Institute of Advanced Engineering and Science, 2014)
In order to satisfy the constantly increasing appetite of consumers for content in today’s world, Personal Video Recorder (PVR) function is implemented in digital TV set-top box (STB) based on Android platform. An algorithm that adjusts video Presentation Time Stamp (PTS) based on audio PTS is presented, which aims at the problem that audio is not synchronized with video existing during playback. And a method of generating index file based on the information of I-picture is presented, which aims at the implementation of trick modes. Namely, the location of I-picture which is used to generate index is recorded while audio and video data are being sent to storage medium in Packetized Elementary Streams (PES) format. The test results show that the TV STB designed can implement synchronization of audio and video accurately and reliably and the recorded programs can be played on the STB at different speeds. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3231